Understanding the Early Impacts of School Mentors’ Ethics of Care on Filipino Gen Z Novice Science Educators’ Informal Professional Learning - Obmerga, Marwin; Yambao, Francis Michael (GILE Journal of Skills Development, 2025)
Care-centric mentorship plays a pivotal role in helping novice educators successfully adapt to the realities of academic institutions. As members of Generation Z begin to enter the teaching profession, they encounter a noticeable lack of formal mentorship and learning platforms tailored to their unique generational characteristics. Consequently, they turn to informal school mentors for guidance and support during this critical phase of their early careers. This study employed a Husserlian phenomenology to uncover the essence of the early impacts of the Ethics of Care provided by school mentors on the informal professional learning of Filipino Generation Z novice science teachers. Ten participants were purposefully selected from a strategic region in the Philippines, employing semi-structured interviews as the data collection method. The field texts were analysed using Colaizzi’s procedural steps to distil the phenomenon’s essence. The findings were validated through the member checking procedure and the critical friend technique. Based on the thematically analysed participants’ interviews, the study introduces the Typology of Ethics of Care-driven Informal Professional Learning, which comprises three distinct learner personas: the Mindful Member, the Grounded Inquirer, and the Utility Thinker. Shaped by caring encounters with informal mentors, each persona encapsulates focal points, fostering antecedents and formative impacts, reflecting their dynamic takeaways. These insights can inform contemporary educational organizations and school mentors in implementing evidence-based mentorship strategies and professional development interventions, ensuring contextual support that empowers this cohort to navigate institutional roles effectively and contribute meaningfully to their educational communities.